2020
DOI: 10.3168/jds.2019-17141
|View full text |Cite
|
Sign up to set email alerts
|

Different distribution of antimicrobial resistance genes and virulence profiles of Staphylococcus aureus strains isolated from clinical mastitis in six countries

Abstract: Staphylococcus aureus is recognized worldwide as one of the main contagious mastitis agents in cattle and can express a set of antimicrobial resistance genes and virulence-associated genes that explain the wide range of outcomes of intramammary infections. Staphylococcus aureus strains are heterogeneous: their different resistance and virulence patterns, associated with hostlevel factors and treatment factors, are related to the severity of infection. The aim of this study was to determine phenotypic antibioti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 62 publications
3
27
1
Order By: Relevance
“…High resistance levels to penicillin and other βlactams among mastitis-causing staphylococci has been described [35][36][37]. In contrast, a lower resistance to penicillin in staphylococci (0-20%) has also been reported in some European countries [38,39] and Canada [7]. Higher resistance rates are likely due to the wide-spread use of penicillin in the treatment of mastitis in dairy cows as observed in the study farms and as evidenced by other previous studies in Kenya [27,40] Further, changes overtime, spatial sampling, differences in antibiotic use and practices might explain discrepancies in resistance levels between regions [33,41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High resistance levels to penicillin and other βlactams among mastitis-causing staphylococci has been described [35][36][37]. In contrast, a lower resistance to penicillin in staphylococci (0-20%) has also been reported in some European countries [38,39] and Canada [7]. Higher resistance rates are likely due to the wide-spread use of penicillin in the treatment of mastitis in dairy cows as observed in the study farms and as evidenced by other previous studies in Kenya [27,40] Further, changes overtime, spatial sampling, differences in antibiotic use and practices might explain discrepancies in resistance levels between regions [33,41].…”
Section: Discussionmentioning
confidence: 99%
“…This higher resistance could be due to the fact that penicillin is still the first-line drug of choice for treatment of mastitis in Kenya [27,34]. Routine culture and identification, coupled with antibiotic sensitivity testing, should be adopted before treatment with antimicrobials to avoid selection pressure of antimicrobial resistant S. aureus [37,39].…”
Section: Discussionmentioning
confidence: 99%
“…Reported frequency of occurrence of the blaZ is variable depending on the region. The data for the USA and Germany are similar, as they are at the level of 41.2% and 47.1%, respectively [7]. On the other hand, information showing this frequency in Brazil is 74.07% [8].…”
Section: Discussion Of the Problemmentioning
confidence: 64%
“…Similarly, as in South Africa, most isolates from the United States (New York State), Argentina and Germany showed resistance to spiramycin (Monistero et al 2020). In contrast to isolates from South Africa, Ethiopia and the United States of America, spiramycin and/or penicillin were not effective in 58% of Italian isolates (Monistero et al 2020). Although the Ethiopian study did not test for spiramycin resistance, very high resistance to penicillin was shown (Kalayu et al 2020).…”
Section: Staphylococcus Aureus Resistance In South Africa Compared To That Of Other Countriesmentioning
confidence: 92%
“…Cosandey et al ( 2016 ) described S. aureus genotype B (GTB) only in Italy, whilst S. aureus genotype R (CLR) and S. aureus genotype C (CLC) were identified in many places in Europe, America and Africa. Genotype CLR, which represents a large cluster containing 13 variants, was detected in all eight countries studied except for Brazil (Monistero et al 2020 ). Cosandey et al ( 2016 ) have shown that S. aureus CLR and CLC clusters are exclusive to dairy cattle and the spread thereof probably started many years ago, when cattle were moved from Europe to other countries (Monistero et al 2018 ).…”
Section: Review Findingsmentioning
confidence: 99%